Using Remote Technology to Engage Patients with Interstitial Lung Diseases in a Home Exercise Program: A Pilot Study - Antonio Sarmento; Kaitlin King; Diana C. Sanchez-Ramirez (Life, 2024)
Introduction: The access and compliance of patients with interstitial lung diseases (ILDs) to exercise programs (EPs) remain challenges. Objectives: We assessed the dropout rate, intervention completion, compliance with data acquisition and submission, safety, and satisfaction of a home EP delivered via video conference (EPVC group) or self-directed (EPSD group) to patients with ILD. Pre- and post-intervention changes in patient outcomes (dyspnea, fatigue, exercise capacity, lung function, and quality of life) were secondarily explored. Material and Methods: Groups performed an eight-week virtual EP three times/week. Video conferences were led by a registered respiratory therapist, whereas self-directed exercises were completed following a pre-recorded video. Participants submitted spirometry, heart rate, and SpO2 results weekly to the research team. Results: Fourteen patients with ILD were equally assigned to the EPVC and EPSD groups, but three from the EPSD group dropped out after the initial assessment (dropout rate of 42.8% in the EPSD group). Eleven patients (mean age of 67 ± 12 years) completed 96.5% of sessions. Compliance with data acquisition and submission was optimal (≥97.6% in both groups), and no adverse events were reported. Changes in overall fatigue severity were significantly different between groups (p = 0.014, Cohen’s r = 0.64). Conclusions: The results suggest that a structured virtual EP delivered via video conference or pre-recorded video can be feasible, safe, and acceptable for patients with ILD.